Prevalence of Non-Communicable Diseases Among Elderly in India: A Scoping Review - Yadav, Patlolla Sriram; Katta, Ajitha; Shirisha, Gooty; Kirtania, Mousami (National Journal of Community Medicine, 2025)
Background: Non-communicable diseases (NCDs) are a growing concern for India's aging population. This scoping review aimed to identify and summarize the prevalence of NCDs among elderly people in India. Methods: A systematic search of PubMed and Google Scholar identified 37 studies published in English between 2013 and 2023 that met the inclusion criteria. Two independent reviewers screened and selected studies, and data was extracted and analyzed using a standardized form. The PRISMA framework was employed to visualize the study selection process. Results: Hypertension was the most prevalent NCD (˃50% in studies), followed by diabetes (<50% in studies, but with high new case detection). Depression was particularly prevalent among urban females (over 50%). Obesity and overweight were widespread, with women being more likely to be overweight and men to have central obesity. Significant gender disparities existed in hypertension, depression, diabetes, and visual impairments. Conclusion: This review highlights the significant NCD burden among elderly Indians, particularly hypertension and diabetes, underscoring the need for targeted health interventions. Addressing modifiable risk factors with gender-sensitive approaches is essential. Further research is needed on the intersection of aging and NCDs in India to improve the quality of life for elderly individuals.